Joseph Conrad's new paradigm for modern man in search of a soul - Koohestanian, Farhang (2013)
Joseph Conrad’s stories, set in all corners of the globe particularly in the Eastern seas and islands, bear resemblance to mythical and archetypal quests in that their protagonists, who are mainly young Westerners, are on the threshold of literal and symbolic journeys into the less explored and the unknown. However, unlike the heroes of myth and classical epic, Conrad’s more or less down-to-earth protagonists represent modern man with his modern concerns and hardships. Conrad was not alone in depicting the miserable human condition of late nineteenth and early twentieth century modernity, but what distinguishes him from his contemporary modernist counterparts is the solution he offers, which parallels the model explored by Carl Gustav Jung during Conrad’s lifetime and subsequently articulated with increasing precision. The new paradigm Conrad portrays becomes evident when his works are studied from a psychological perspective and in chronological order of composition. This approach reveals the gradual formation of a significant pattern comparable to what occurs in recurrent dreaming and very similar to the process that Jung defines as ‘individuation’. Almayer’s Folly, An Outcast of the Islands, Lord Jim, “The Secret Sharer”, and The Shadow-Line narrate the stories of five young men on journeys of self-discovery, of individuation, journeys which involve an exploration of the unconscious. In the first three works, Conrad criticises two opposite but equally detrimental extreme reactions to modern life: firstly, extreme rationalism and positivism which closes the door to the unconscious, rejecting it as irrational and primitive; secondly, the antithesis to this approach, where the protagonists fall under the absolute control of the unconscious. The outcomes of such rejection of or submission to the unconscious are seen to be tragically disastrous and inadequate approaches to modern experience. However, that is not the whole story and in the last two of these works Conrad synthesises a novel paradigm for modern man in search of a soul. He shows that the individual, like an adept captain, must be ready to sail the sea of the unconscious, to encounter what may lie there, and return to the land, return to consciousness. Conrad’s works not only provide the road map to individuation for all human beings, irrespective of time, place and race, they themselves individuate.